ASF Exit Strategy: Providing cumulative evidence of the absence of African swine fever virus circulation in wild boar populations using standard surveillance measures - European Food Safety Authority (EFSA); Søren Saxmose Nielsen; Julio Alvarez; Dominique Joseph Bicout; Paolo Calistri; Klaus Depner; Julian Ashley Drewe; Bruno Garin‐Bastuji; Jose Luis Gonzales Rojas; Christian Gortazar Schmidt; Mette Herskin; Virginie Michel; et al. (EFSA Journal, 2021)
Abstract EFSA assessed the role of seropositive wild boar in African swine fever (ASF) persistence. Surveillance data from Estonia and Latvia investigated with a generalised equation method demonstrated a significantly slower decline in seroprevalence in adult animals compared with subadults. The seroprevalence in adults, taking more than 24 months to approach zero after the last detection of ASFV circulation, would be a poor indicator to demonstrate the absence of virus circulation. A narrative literature review updated the knowledge on the mortality rate, the duration of protective immunity and maternal antibodies and transmission parameters. In addition, parameters potentially leading to prolonged virus circulation (persistence) in wild boar populations were reviewed. A stochastic explicit model was used to evaluate the dynamics of virus prevalence, seroprevalence and the number of carcasses attributed to ASF. Secondly, the impact of four scenarios on the duration of ASF virus (ASFV) persistence was evaluated with the model, namely a: (1) prolonged, lifelong infectious period, (2) reduction in the case‐fatality rate and prolonged transient infectiousness; (3) change in duration of protective immunity and (4) change in the duration of protection from maternal antibodies. Only the lifelong infectious period scenario had an important prolonging effect on the persistence of ASF. Finally, the model tested the performance of different proposed surveillance strategies to provide evidence of the absence of virus circulation (Exit Strategy). A two‐phase approach (Screening Phase, Confirmation Phase) was suggested for the Exit Strategy. The accuracy of the Exit Strategy increases with increasing numbers of carcasses collected and tested. The inclusion of active surveillance based on hunting has limited impact on the performance of the Exit Strategy compared with lengthening of the monitoring period. This performance improvement should be reasonably balanced against an unnecessary prolonged ‘time free’ with only a marginal gain in performance. Recommendations are provided for minimum monitoring periods leading to minimal failure rates of the Exit Strategy. The proposed Exit Strategy would fail with the presence of lifelong infectious wild boar. That said, it should be emphasised that the existence of such animals is speculative, based on current knowledge.